Arterialised earlobe blood gas analysis: an underused technique. Issue 4 (April 1994) - Pitkin, A D; Roberts, C M; Wedzicha, J A
Abstract : BACKGROUND--Techniques for sampling arterialised capillary blood from the finger pulp and the earlobe were first described over two decades ago but, although close agreement between arterial values and earlobe samples has been demonstrated in normal subjects, this technique is not in common usage. METHODS--Forty patients with chronic lung disease and a wide range of arterial blood gas values were studied. Simultaneous earlobe and arterial samples were drawn with the patient at rest and analysed in the same blood gas analyser. The respiratory function laboratory staff in 50 UK hospitals with a respiratory department were telephoned and asked whether the technique was used in their hospital and the reasons, if known, for not adopting it. RESULTS--Earlobe and arterial blood gas tensions agreed closely over a wide range of values of arterial pH, PCO2 (mean difference 0.21, 95% confidence intervals -0.24 to +0.67 kPa) and PO2 (mean difference -0.17, 95% confidence intervals -1.09 to +0.75 kPa), especially at arterial PO2 values lower than 8 kPa. Of 50 UK centres surveyed 18% used the arterialised earlobe technique and 4% had plans to introduce it. Reasons for not using it were lack of knowledge in 64%, no blood gas analyser in 6%, the technique was considered inaccurate in 4%, and insufficient staff in 4%. CONCLUSIONS--Although earlobe blood gas analysis is sufficiently accurate to be reliably substituted for arterial sampling in routine clinical practice, most centres in the UK do not use the technique. The main reasons for this appear to be lack of knowledge of its existence and uncertainty over its accuracy.